jenis jenis capung (odonata:anisoptera) di desa sei dua indah kecamatan rambah hilir kabupaten rokan hulu propinsi riau - Yanti, Rahmah (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
Dragonflies (Anisoptera) are one group of Arthropods that have medium lage size and atraktive colors. This study aims to determine the types of dragonflies (Odonata: Anisoptera) which contained in Sei Dua Indah Subdistrict Rambah Hilir, Rokan Hulu Riau Province. This study was conducted from November to December 2015 using a survey method. Dragonfly that hen identified by describing the types of the dragonflies obtained. Results of the study found 2 the families, 10 a genera and species of 11 with a total of 32 individuals. As for the types of dragonflies obtained is Ictinogomphus rapax, Ictinogomphus decoratus, Branchythemis contaminata, Brachydiplax subrina, Cratilla lineata, Lathrecista asiatica, Neurothemis fulvia, Orthetrum sabina, Pantala flavescens, Potamarcha congener, and Rhyothemis phyllis.Keywords : Anisoptera, Dragonflies Species,